Exploring Directive Speech Acts in Elementary School Communication in Kolaka: Language Pedagogy Implications - Nur Ihsan HL; Samsuddin Samsuddin; Hendri Yawan; Yuliati Yuliati (International Journal of Language Education, 2023)
This sociopragmatics study aims to investigate the various types of directive speech acts and the markers of local wisdom in the communication of elementary students in  Kolaka. The research design employed is qualitative descriptive, chosen for its ability to describe the types of directive speech acts and the manifestation of local wisdom within the context of elementary school students. The participants in this study consisted of elementary school students from Kolaka Regency. Data were collected through non-participant observation, and the analysis followed qualitative data procedures based on the interactive model developed by Miles and Huberman, which involved data reduction, data presentation, and drawing conclusions. The findings revealed four types of directive speech acts commonly used by elementary school students: demanding, commanding, begging, and challenging. These directive speech acts were found to be influenced by the cultural context, specifically manifested through the use of clitics. The clitics -ko, -mi, -ka, -hae, and -na were identified as significant markers of the local wisdom in the communication of elementary students, observed in utterances such as lihatko, ayomi, pindahko, biarmi, siniko, and jemputna. These clitics not only serve as markers of cultural identity but also indicate different levels of politeness in communication.  Further implications for language teaching practices are also discussed.